miR-20b-5p, TGFBR2, and E2F1 Form a Regulatory Loop to Participate in Epithelial to Mesenchymal Transition in Prostate Cancer - Qi, Jin-Chun; Yang, Zhan; Zhang, Yan-Ping; Lu, Bao-Sai; Yin, Yue-Wei; Liu, Kai-Long; Xue, Wen-Yong; Qu, Chang-Bao; Li, Wei (Frontiers in Oncology, 2020)
The transcription factor E2F1 regulates the expression of miR-20b-5p precursor and is involved in epithelial-to-mesenchymal transition (EMT). TGF-β1 induces EMT in prostate cancer (PCa) by binding to TGF-beta receptor 2 (TGFBR2) to activate the TGF-β signaling. However, the relationship between TGFBR2, E2F1and miR-20b-5p in the modulation of the EMT of PCa cells remains unknown. In this study we found the level of miR-20b-5p expression was significantly lower in PC3 and DU145 cells than that of prostate epithelial (RWPE-1) cells, and TGF-β1 treatment further downregulated miR-20b-5p expression in these two cell lines. Functional studies showed that miR-20b-5p suppressed TGF-β1-induced migration and invasion of PC3 and DU145 cells by upregulating E-cadherin and downregulating vimentin, thus leading to TGF-β1-induced inhibition of EMT. Using gain and loss of function experiments, it was showed that E2F1 mediated TGF-β1 regulation of miR-20b-5p expression. Further, luciferase activity assay showed that TGFBR2 was a direct target of miR-20b-5p in PCa cells. These results suggested that miR-20b-5p, TGFBR2 and E2F1 formed a regulatory loop to modulate EMT induced by TGF-β1. A novel regulatory mechanism underlying miR-20b-5p/TGFBR2/E2F1 axis is involved in TGF-β1-induced EMT of PCa cells, and miR-20b-5p may probably be a potential therapeutic target for PCa.